2020
DOI: 10.1016/j.chest.2020.08.336
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Healthcare-Associated Infections in the United States

Abstract: To explore the racial and ethnic differences in the occurrence of healthcare-associated infections (HAIs) captured using the most recent available National Inpatient Survey (NIS) data for 2016-2017. METHODS: Using merged NIS data from 2016-2017, for adult patients (18 and above), 9 HAI measures-surgical site infection (SSI), central line-associated bloodstream infections (CLABSI), catheter-associated urinary tract infection (CAUTI), ventilatorassociated pneumonia (VAP), hospital-acquired pneumonia (HAP), methi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our study identified demographic factors, chronic conditions, and acute presentations that providers could be cognizant of while gauging risk of ICU-onset BSI. Black and Hispanic patients displayed a higher risk for ICU-onset BSI compared with White patients further widening existing healthcare disparities even around healthcare-associated conditions (32, 33). Chronic conditions including neurologic and hepatic disorders, coagulopathy, arrhythmias, weight loss, and acute presentations such as trauma, acute respiratory, and gastrointestinal dysfunction were associated with acquisition of ICU-onset BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified demographic factors, chronic conditions, and acute presentations that providers could be cognizant of while gauging risk of ICU-onset BSI. Black and Hispanic patients displayed a higher risk for ICU-onset BSI compared with White patients further widening existing healthcare disparities even around healthcare-associated conditions (32, 33). Chronic conditions including neurologic and hepatic disorders, coagulopathy, arrhythmias, weight loss, and acute presentations such as trauma, acute respiratory, and gastrointestinal dysfunction were associated with acquisition of ICU-onset BSI.…”
Section: Discussionmentioning
confidence: 99%